DAMPAK PENGAJIAN KITAB MINHAJ AL MUTA’ALLIM PADA BULAN RAMADHAN TERHADAP JIWA WIRAUSAHA MASYARAKAT LOKAL - ZAKIYATUL; Zakiyatul Abidah (Jurnal Adab dan Peradaban Islam, 2025)
This study aims to analyze the impact of studying the Minhāj al-Muta'allim book during Ramadan on the formation of an entrepreneurial spirit in the community of Banjaranyar Village, Paciran, Lamongan. In a competitive economic dynamic, entrepreneurship is not understood solely as an economic activity, but as a manifestation of work ethic and social responsibility based on Islamic spiritual values. The Ramadan recitation activities in Banjaranyar are a strategic moment for instilling Islamic values that shape ethical and productive entrepreneurial character. The research method applied a qualitative approach with a phenomenological-cultural case study design to comprehensively describe the spiritual experiences and economic behavioral transformations of the community. Data collection was conducted through participatory observation, in-depth interviews with recitation participants and business actors, and documentation of Ramadan recitation activities. The research findings show that Minhāj al-Muta'allim recitation plays a crucial role in instilling the values of sincerity, honesty, tawakal (trust in God), and brotherhood, which significantly strengthen the Islamic work ethic and entrepreneurial spirit of the community. The recitation activities also build social solidarity and a strong trust-based economic network, which contributes to the economic independence and competitiveness of the local community. These findings confirm that strengthening spiritual values through religious education can be an effective and sustainable model for Islamic-based socio-economic empowerment. This research has implications for the formulation of community economic policies based on morality, spirituality, and local wisdom in responding to the challenges of modernity.